Restructuring the International Textile Production and Trade Network. The Role of Italy and Portugal - Marlies Schütz; Nicole Palan (FIW - Research Centre International Economics, 2015)
Production and trade processes in the textile industry have been undergoing tremendous changes in structure due to both changes in technology (i.e. increased mechanization and automation processes) and in the institutional environment (i.e. the assignment of the WTO treaty in 1994). This paper studies the restructuring process in the textile industry from the perspective of two major textile producing countries in the EU15, i.e. Italy and Portugal between the two years 1995 and 2009. As a starting point, a detailed descriptive analysis of the global distribution of the textile industry and changes therein is provided. By means of two international textile trade networks (ITTNs), showing (1) trade in value added and (2) trade in labour, we next discuss spatial trade patterns and changes therein. Focusing on the ITTNs, we then figure out how these countries' textile industries were affected in terms of specialisation patterns, movements along the global value chain and vertical specialisation. Combining the merits of a multiregional I/O-framework with network analysis both qualitative and quantitative aspects of the experienced restructuring process are figured out. This paper contributes to a better understanding of changes in national economic structures resulting from changes in the institutional and technological change without masking the international context.
Keywords: C67; F14; O12; 330; International trade network; concentration; textile industry; structural change; network analysis; multiregional input-output model